The differences in the width of male and women maxillary sinus seen from panoramic radiography in tribe Students Minang Faculty of Dental Medicine, Baiturrahmah University - Resti Iswani; Rizki Wulandari; Hamdy Lisfrizal; Firdaus (Journal of Dentomaxillofacial Science, 2021)
Objective: The purpose of this study was to determine whether there is a difference in the width of the maxillary sinus between male and female students of the Minang ethnic group, Faculty of Dentistry, Baiturrahmah University, seen from panoramic radiographs.Material and Methods: This study is an analytical study with a sample size of 50 respondents using purposive sampling method. The data analysis is displayed using the frequency distribution table and the significance level using the SPSS program with the independent t-test.Results: The results showed that the mean value of the width of the right maxillary sinus in men was 35.06 mm (CI 1.7381 ± 6.4219), while in women it was 30.98 mm (CI 1.7378 ± 6. 4232). The mean value of the left maxillary sinus width in men was 35.38 mm (CI 2.6736 ± 6.6464), while in women it was 30.72 mm (CI 2.6732 ± 6.6469).Conclusion: The conclusion of this study is that there is a significant difference between the width of the maxillary sinuses of men and women in Minang ethnic students, Faculty of Dentistry Baiturrahmah University with a p value <0.05.